PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY DENGAN APLIKASI ASSEMBLR STUDIO PADA PENGENALAN KONSTRUKSI BANGUNAN MUSHOLA APUNG - Rayhan Akbar Wiguna; Kinanti Wijaya (Jurnal Teknik dan Teknologi Indonesia, 2023)
Indonesia has about 81,000 km of coastline making coastal areas of great significance to the Indonesian economy. Development in coastal areas is very important to provide an improved quality of life to coastal communities with the development of health services, education, infrastructure to places of worship such as mosques/mushola. The platform structure of a floating mosque or mushola building is unique in its platform part, which resembles a building on stilts. Based on the data obtained, the majority of students do not understand the type of floating building construction. Therefore, product development on the construction of floating prayer rooms with interactive augmented reality (AR) based learning media using the Assemblr Studio application and developed with the 4D model consisting of the stages of define, design, develop, and disseminate. The product in the form of this media is intended to display a 3D model in the form of an architecturally floating mushola building with illustrations of the surrounding environment, displaying a 3D model in the form of a structure of a floating mushola building along with its explanation, displaying supporting videos in the form of building renderings and structural development stages of a floating mushola building. This learning media has gone through validity testing by material experts and media experts and obtained a feasibility score of 4.14 (predicate feasible) for the material validation test and obtained a feasibility score of 4.17 (predicate very feasible) for the media validation test.